Merleau-Ponty e a crise da razão - Marques, Rodrigo Vieira (Universidade Federal de São Carlos, 2011)
ABSTRACT This work takes its point of departure in Merleau-Ponty s Philosophy, centered in the notion of Crisis of Reason , basing itself on the presupposition that this is a fundamental concept of contemporary phenomenology. In the Cartesian thought, already it was possible to find the idea of the crisis, however, it was the finding of a crisis of sciences . Something similar was also in Valery, especially when he speaks of a crisis of spirit . The novelty of Husserl was exactly in showing that the crisis, as he lived it, was deeper, shook the Reason itself. This work assumes the task of showing that, not limiting to a crisis of sciences, of the spirit or of Reason itself, Merleau-Ponty discusses a present crisis in the man himself, or rather, in the diverse points of view that has about him. In this sense, his philosophical project is based, primarily, on the attempt to establish a dialogue with the points of view of the philosophy and of the science. Therefore, an inquiry of the divergence of these points, is warranted, elucidating not only the scenario in which the conflict is, but also its genesis. Likewise, starting from a Merleau-Pontian understanding of the crisis, finally, this study also assumes the task of asking about the repercussions of this crisis in the relation of philosophical knowledge to itself, then, in the way of his own philosophy to understand its history, being, therefore, the importance of this incursion in the desire to explain what, according to Merleau-Ponty, would be a possible way of overcoming.
Keywords: Filosofia francesa; Merleau-Ponty, Maurice, 1908- 1961; Fenomenologia; French Philosophy; Maurice Merleau-Ponty; Phenomenology; CIENCIAS HUMANAS::FILOSOFIA